An experimental study on the energy absorption characteristics of single- and bi-layer cups under quasi-static loading. Issue 3 (4th May 2019) - Ghasemabadian, M. A.; Kadkhodayan, M.; Altenhof, W.; Bondy, M.; Magliaro, J.
ABSTRACT: Experimental testing was conducted to study the mechanical behaviour and energy absorption characteristics of single- and bi-layer cups under axial quasi-static compressive loading. Bi-layer plates were fabricated by explosive welding or joined by adhesive and were formed by a deep drawing process to produce the cup . The tests were performed at a rate of 10 mm/min. The effect of geometric parameters and other apparatus parameters were considered in this study. Results from the experimental tests showed that the layer order of the bi-layer cup significantly influences energy absorption capacities of the cup such that the structures with stainless steel as the outer layer has total absorbed energy and mean crush force 8% and 14% higher, respectively, than those of cups with the aluminium outer layer. Furthermore, it was observed that cups fabricated by explosive welding displayed mean crush force and specific energy absorption 1.5 times greater than those fabricated with adhesive.